Aerodynamic and thermal properties of melon (Citrullus lanatus) seeds under varying drying temperature for separation from shells and processing - Asoiro, F. U.; Simeon, M. I.; Ezugwu, I. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The effect of temperature on aerodynamic and thermal properties of melon seed is very important in the design of drying, processing and storage equipment. To this end, some thermal and aerodynamic properties of melon seed were investigated as a function of temperature. The thermal conductivity, specific heat capacity and thermal diffusivity were the thermal properties that were determined. Terminal velocity, seed drag force and drag coefficient were the aerodynamic properties investigated. The results obtained for the terminal velocity of the seed at temperatures of 30ºC, 35ºC, 40ºC, 45ºC, 50ºC, 55ºC, 60ºC, 65ºC, 70ºC, and 75ºC were 7.415, 7.135, 6.32, 9.95, 5.885, 5.62, 5.32, 5.205, 4.88m/s respectively. The values continued to reduce until 100ºC with a value of 3.37m/s. The drag force of the melon seed attained its maximum value at temperature of 50ºC (1.777N). A minimum value was attained at the temperature of 100ºC (0.343N). At various temperature levels of 35ºC, 40ºC, 45ºC, 55ºC, 60ºC, 65ºC, and 70ºC, values for drag force were 1.472N, 1.349N, 1.275N, 1.079N, 0.981N, 0.883N, and 0.884N respectively. The drag coefficient was at its maximum at temperature of 80ºC with a value of 1.179, and minimum at 30ºC with a value of 0.743. For the thermal properties, the specific heat capacity attained a maximum value of 2.995KJ/Kg/K at a temperature of 30ºC, while it attained a minimum value of 1.596KJ/Kg/K at temperature of 100ºC. The thermal conductivity was maximum at 30ºC with a value of 3.62W/m/K, and minimum at 100ºC with a value of 0.46W/m/K. In the same vein thermal conductivity reduces with an increase in temperature. At the temperatures of 30ºC, 35ºC, 40ºC, 45ºC, 50ºC, 55ºC, 60ºC, 65ºC, 70ºC, 75ºC, and 80ºC, the thermal conductivity values were 3.26W/m/K, 1.545W/m/K, 1.1W/m/K, 1.83W/m/K, 1.725W/m/K, 0.64W/m/K, 0.605W/m/K, 0.555W/m/K, 0.53W/m/K, 0.52W/m/K, and 0.505W/m/K respectively. The thermal diffusivity attained a maximum value at 30ºC (6.19×10-5m2/s) and a minimum value of 1.16×10-6m2/s at 100ºC. Therefore, it can be clearly observed that temperature has a very great effect in the aerodynamic and thermal properties of egusi melon and these values are vital to engineers and food processors in the design of storage and processing equipment for melon seeds.